EKSPLORASI DAN UJI SENYAWA BIOAKTIF BAKTERI AGENSIA HAYATI UNTUK PENGENDALIAN PENYAKIT KRESEK PADA PADI - Sri Kurniawati; Kikin Hamzah Mutaqin; Giyanto . (Universitas Lampung, 2015)
Exploration of bacterial biocontrol agent and its potential bioactive compound to control rice bacterial leaf blight. The research aims were to obtain bacterial isolates which were potential as biological control agent of X. oryzae pv. oryzae, the causal agent of rice bacterial blight and to assess the effectiveness of their bioactive compounds, and to identify of the potential isolates. The research steps included bacterial isolation, screening based on antibiosis activity and pathogenicity test, characterization based on chitinolytic enzyme production, siderophores, and phosphate dissolution test, effectiveness test of bioactive compounds and molecular identification of potential isolates. Out of 156 bacterial isolates from rice crop tested, 11 isolates showed to be non plant pathogenic and to have activity as biological agents against X. oryzae pv. oryzae pathotype III, IV and VIII. Further characterization of 11 isolates resulted in 2 isolates that showrd ability to produce chitinase (isolates T5-1118 and R7-1018), phosphatase (isolates T5-1105 and T6-1109), and siderophores (isolates T5-1118 and T6- 1109). The test of bioactive compound effectiveness of 4 isolates to the growth of X. oryzae pv. oryzae showed thatT5-1118, T5-1105, T6-1109 and R7-1018 have ability to inhibit X. oryzae pv. oryzae at 48 hours after inoculation of 66,61%, 62,4%, 23,97% and 12,40%, respectively. Identification of 4 bacterial biocontrol isolates with partial sequencing of 16S rRNA gene showed that those bacteria are close to Bacillus nealsonii strain F22 (R7-1018), Chromobacterium sp. MWU328 (T5-1118), Streptomyces sp. Antag 1 (T5-1105) and Kitasatospora nipponensis strains H2-4 (T6-1109).